PENDIDIKAN ISLAM SEBAGAI KONSEP DASAR NASIONALISME STUDI KOMPARASI PERSPEKTIF IR. SOEKARNO DAN KH. ABDUL WAHAB HASBULLAH - Ela, Rosyida; Maulida Septiana, Arbyanti; Ahsanu, Amala (ASWALALITA: Journal of Da'wah Management, 2022)
Abstrac Education is the main key in the formation of the spirit of nationalism of the Indonesian people. Because until now education is believed to be the most powerful means for the process of transforming values, including the values ​​of nationalism in Islam. Soekarno and KH. Abdul Wahab Hasbullah? (2) How is the implementation of Islamic education towards nationalism according to Ir. Soekarno and KH. Abdul Wahab Hasbullah on education today?. Based on the formulation of the problem, this researcher aims (1) to describe Islamic education as the basic concept of nationalism thought by Ir. Soekarno and KH. Abdul Wahhab Hasbullah. (2) To describe the implementation of Islamic education on nationalism according to Ir. Soekarno and KH. Abdul Wahab Hasbullah on current education. This study uses a qualitative approach, the type of research is library research, constant comparative analysis. From the results of this study it can be concluded that, Islamic education as the basic concept of nationalism thought Ir. Soekarno and KH. Abdul Wahab Hasbullah, namely the balance of logic and taste; tolerance; liberation; patriotism; humanism; pluralism; unity. Which of these concepts can be implemented in education at this time.